2022
DOI: 10.1111/iji.12584
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin‐1 receptor antagonist (IL‐1ra) VNTR, gene polymorphism and breast cancer susceptibility in Iranian population: Experimental and web‐based analysis

Abstract: Breast cancer is one of the leading causes of cancer mortality. Growing evidence indicates that interleukins and its polymorphisms are involved in the pathogenesis of breast cancer. Variable number of tandem repeat (VNTR) polymorphism can affect transcription rate, mRNA stability and also the resulting protein expression and activity. Hence, present study aimed to assess the possible association between interleukin-1 receptor antagonist (IL-1Ra) VNTR polymorphism, and breast cancer susceptibility in Iranian po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In this regard, multiple studies have found a link between ovarian cancer, gastric cancer, and IL-1 gene polymorphisms ( Abbasian et al, 2018 , Raza et al, 2020 , Nahar et al, 2022 ). Additionally, numerous researches have assessed the association between BC and IL-1 gene polymorphisms ( Ibrahimi et al, 2022 , Al-Eitan et al, 2020 , Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, multiple studies have found a link between ovarian cancer, gastric cancer, and IL-1 gene polymorphisms ( Abbasian et al, 2018 , Raza et al, 2020 , Nahar et al, 2022 ). Additionally, numerous researches have assessed the association between BC and IL-1 gene polymorphisms ( Ibrahimi et al, 2022 , Al-Eitan et al, 2020 , Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%